Investigating the impact of play therapy on social cooperation, social interaction and social independence behaviors of children staying at women’s shelter homes (Annals of Medical Research, 2021)
Aim: The purpose of the study is to determine whether the play therapy has an effect on the social skills behaviors in the children aged three-six years who exposed to various traumatic situations and living with their mother in the women shelter homes.Material and Methods: The study is an experimental study in which experimental - control group, pre-test, post-test and follow - up measurements were made. ‘’Parent-Child Information Form’’ and ‘’Preschool and ‘’Kindergarten Behavior Scale (PKBS-2)’’ were used as data collection tools. Analyzes were evaluated non-parametrically with the IBM SPSS 21 package program.Results: The results show that there is an increase in social skills of children in experimental group. The effect of the implementation was observed in social cooperation, social interaction and social independence behaviors of children who attend the play therapy.Conclusion: The significant difference in the social skills scale-total scale post test scores between the children in the experimental group who participated in play therapy and the children in the control group points to the effectiveness of play therapy in social skills acquisition by children. The number of sessions should be increased and the participation of mothers should be ensured as factors that increase the effectiveness of play therapy.Keywords: Children In Women’ Shelter Homes; Play Therapy; Social Skills.
Keywords: Children In Women’ Shelter Homes; Play Therapy; Social Skills.